The correlation between Body Mass Index and Body Image Dissatisfaction and Body Image Perception in young Saudi women - Aljadani, Haya M (Progress in Nutrition, 2019)
Background/ aims: Staying healthy may become a challenge, especially for young women, as they tend to focus on their body image and weight gain. Greater body size links to body image dissatisfaction, among young women. The prevalence of BID influences by many factors including culture. Therefore, this research aimed to; (1) explore the prevalence of Body Image Dissatisfaction (BID), and body image perception across Body Mass Index (BMI) categories; and (2) explore the correlation between BMI and BID among a sample of Young Saudi women (n=226) who live in Makkah region. Methodology: A self-administrative questionnaire was used for data collection on social-demographic and anthropometric measurements, and a figure rating scale of 9 graphics of body shape by Stunkard et al. was used to measure the BID and body image perception. The BID score was calculated as the differences between the perceived current image and ideal image. Body image perception was calculated as the differences between perceive body image and actual BMI. BMI for each participant was calculated from self-reported weight and height. Results: The participants were 226 young women with an age range from 18 to 35 years. The findings indicated that BMI positively correlated with BID, but this correlation was small with r=0.135, P value > 0.01. Even though the prevalence of overweight and obesity was low (23%), the prevalence of BID was high (80.5%). Of those who classified as healthy weight, 57.6% wanted to lose weight, while 17.3% wanted to add weight. The majority of participants (61.5%) adequately estimated their BMI, while 28.3% underestimated their weight and 10% overestimated it. All the obese and 32% of the overweight underestimated their BMI, while 20% of underweight participants overestimated their BMI. Conclusion: The findings indicated that most of the young women were dissatisfied with their weight, even if it is within normal BMI, and had a misconception about their healthy weight.